Industri kecil batu bata di Kabupaten Sidenreng Rappang Provinsi Sulawesi Selatan - Panennungi Panennungi; Anwar Fatah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The purpose of this Community Partnership Program is improve the knowledge and ability of the involved community in running their business, whether on the production and management aspect. This program is expected to give proper knowledge and skill to improve: 1) the quantity of bricks, 2) the quality of bricks, 3) the management and marketing, and 4) product sales. In order to overcome the problem, several methods are employed in this program, such as: 1) lecturing and question and answer (Q&A) session toenhance communities’quantity of bricks, 2) lecturing, Q&Asession, tutorial, and training to enhance communities’ quality of bricks, 3) lecturing and question and answer session to enhance management and marketing skill, and 4) lecturing,Q&A session, tutorial, and training to improve communities’product sales. The result of this Community Partnership Program shows that the communities are skilled and educated to improve their product quantity, product quality, management and marketing, and product sales.